Computational fluid dynamics (CFD) validation and investigation the effect of piston bowl geometries performance on port fuel injection-homogeneous charge compression ignition (PFI-HCCI) engines - Nik Ab Rashid, Nik Muhammad Hafiz; Hairuddin, Abdul Aziz; Md Rezali, Khairil Anas; Masuri, Siti Ujila; Al Anbagi Muntasser, Abdulabbas Mossa; Jamiluddin, Jaafar; Deni Fajar, Fitriyana (Semarak Ilmu Publishing, 2024)
Homogeneous charge compression ignition (HCCI) is an advanced combustion strategy proposed to provide higher efficiency and lower emissions than conventional compression ignition. Nevertheless, the operation of HCCI engines still presents formidable challenges. Preparing homogeneous mixtures and controlling the combustion phase are crucial challenges in the context of engine performance. Piston bowl geometry significantly enhances the process by improving the flow and facilitating air-fuel mixing for combustion. On that note, this study utilised the CFD simulation methods to analyse HCCI combustion in port fuel injection (PFI) mode and evaluate the effect of piston bowl geometries on engine performance. For this purpose, the CFD simulation result for a single-cylinder, four-stroke YANMAR diesel engine was validated with experimental data. The different piston bowl geometries with the same volume, compression, and equivalence ratio were then investigated numerically. The validation result of the CFD simulation offers enough confidence to continue the study with different piston bowl geometries. The results attained from the Direct Injection (DI) engine piston bowl application demonstrate a minor change in in-cylinder pressure and heat release rate. The piston bowl design employed in a Port Fuel Injection engine application exhibited different combustion phases while demonstrating similarity in attaining in-cylinder pressure. The findings for swirl induce piston bowl design indicate an enhancement of in-cylinder pressure for the Spiral Crown geometry model, reaching 9.42 MPa. The results of the study demonstrated that the piston bowl's design affected the performance of an HCCI engine.